1983
DOI: 10.3109/03009748309102890
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rheumatoid Arthritis with Prostaglandin E1, Precursors CIS-Linoleic Acid and γ-Linolenic Acid

Abstract: 20 patients with active rheumatoid arthritis were treated for 12 weeks with the prostaglandin E1 precursors cis-linoleic acid and gamma-linolenic acid in the form of primrose evening oil (Efamol) and the co-factors zinc, ascorbic acid, niacin, and pyridoxin (Efavit). There was a slight fall in skin reactivity to UV light during the treatment, but no effect on plasma or urine concentrations of PGE1, cAMP or cGMP. There was no effect of the treatment on ESR, P-fibrinogen, number of tender joints, number of swoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…Unfortunately, fatty acid analyses of the 15 month samples were not carried out so this hypothesis remains unchecked. The results from our work appear to be in contrast with those obtained by Brown et al16 and Hansen et al 17 Both these studies used a lower dosage regimen of EPO and in both the study period was only three months. As can be seen from our data, improvement is most marked from six months onwards.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, fatty acid analyses of the 15 month samples were not carried out so this hypothesis remains unchecked. The results from our work appear to be in contrast with those obtained by Brown et al16 and Hansen et al 17 Both these studies used a lower dosage regimen of EPO and in both the study period was only three months. As can be seen from our data, improvement is most marked from six months onwards.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar beneficial effects on RA have been reported following a supplementation with blackcurrant seed oil, containing 525 mg day −1 GLA (Watson et al ., 1993). Two trials examining whether EPO supplements could reduce the clinical symptoms of RA and the dosage of NSAIDs used by patients with RA found mild improvements in symptoms and reduction in NSAIDs (Belch et al ., 1988; Brzeski et al ., 1991) whereas others have found no positive effects (Hansen et al ., 1983; Darlington & Stone, 2001). One of the above trials, reporting a positive effect of EPO, found a reduction in NSAIDs usage in both the placebo and intervention arms (reduction of 400 mg ibuprofen per day) (Brzeski et al ., 1991).…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 92%
“…We now know that this dose is unlikely to produce benefit, and indeed this study was negative. In another study by Hansen et al (1983), there was a trend towards improvement in the EPO group, despite a lower dosage regimen being utilized. In both these studies, the time period evaluated was only 3 months, and it is likely that a minimum of 4-6 months is required for therapeutic benefit to become apparent.…”
Section: N-6 Essential Fatty Acids and Rheumatoid Arthritismentioning
confidence: 96%